2017
DOI: 10.1093/femsyr/fox037
|View full text |Cite
|
Sign up to set email alerts
|

Designing microorganisms for heterologous biosynthesis of cannabinoids

Abstract: During the last decade, the use of medical Cannabis has expanded globally and legislation is getting more liberal in many countries, facilitating the research on cannabinoids. The unique interaction of cannabinoids with the human endocannabinoid system makes these compounds an interesting target to be studied as therapeutic agents for the treatment of several medical conditions. However, currently there are important limitations in the study, production and use of cannabinoids as pharmaceutical drugs. Besides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 102 publications
0
67
0
Order By: Relevance
“…To form the unique PA structure, a critical enzyme, aromatic prenyltransferase (aPTase), catalyzes the condensation reaction between a prenyl chain and an aromatic ring to yield the PA (Figure ). As most aPTases from plants are integral membrane proteins (Carvalho, Hansen, Kayser, Carlsen, & Stehle, ), this key enzyme also represents a major challenge in the development of a microbial platform for the synthesis of PAs as its functional heterologous expression is required to actively catalyze the prenylation reaction. As such, many proof of concept studies reconstituting PAs biosynthetic pathways have been done in eukaryotic cells (yeast; Z. Li et al, ; Zirpel, Degenhardt, Martin, Kayser, & Stehle, ), and even these efforts have been limited to whole‐cell biotransformations with low product yields.…”
Section: Introductionmentioning
confidence: 99%
“…To form the unique PA structure, a critical enzyme, aromatic prenyltransferase (aPTase), catalyzes the condensation reaction between a prenyl chain and an aromatic ring to yield the PA (Figure ). As most aPTases from plants are integral membrane proteins (Carvalho, Hansen, Kayser, Carlsen, & Stehle, ), this key enzyme also represents a major challenge in the development of a microbial platform for the synthesis of PAs as its functional heterologous expression is required to actively catalyze the prenylation reaction. As such, many proof of concept studies reconstituting PAs biosynthetic pathways have been done in eukaryotic cells (yeast; Z. Li et al, ; Zirpel, Degenhardt, Martin, Kayser, & Stehle, ), and even these efforts have been limited to whole‐cell biotransformations with low product yields.…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesis of unique compounds such as cannabinoids, terpenes and flavonoids in non-Cannabis organisms is gaining much interest as an industry or the research. Attempts for synthesizing THC and CBD in yeast and microorganisms are actively researched (Carvalho et al 2017). Heterologous production of isoprenoid, a large family of secondary metabolites, has been successful in both yeast and E.coli (Paddon and Keasling 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For the latter possibility, it was recently shown that the tetrahydrocannabinolic acid (THCA)forming enzyme [7] in combination with a soluble prenyltransferase can be simultaneously produced in Saccharomyces cerevisiae and Komagataella phaffii in their active form [8]. This marks an important step towards the total biosynthesis of cannabinoids in a microbial platform organism and was recently reviewed in detail elsewhere [9].…”
Section: Current Perspectives On Biotechnological Cannabinoid Productmentioning
confidence: 99%